A public policy proposal: organ donation culture program in Morelia, Michoacán, México - Zamora Torres, América Ivonne; Díaz Barajas, Yesica (Población y Salud en Mesoamérica, 2021)
Although in our times organ transplantation is already a routine medical procedure that represents in most of cases the only alternative for waiting list patients continue living, the problem in the city of Morelia, Michoacán, is similar to that which occurs around the world, the lack of organ donation culture, do not let people in favor of it, put into practice their preferences, showing a high percentage of family rejections when consent for donation is requested. The objective of this work was the design of a public policy using the rational approach, with the Logical Framework Matrix methodology, resulting in a proposal for a post mortem organ donation culture program in Morelia, Michoacán, in order to reduce these refusals and improve the level of organ donations and transplants.